China Stroke Registry for Patients With Traditional Chinese Medicine (CASES-TCM): Rationale and Design of a Prospective, Multicenter, Observational Study - Feng, Luda; Kong, Lingbo; Dong, Xinglu; Lai, Xinxing; Zhang, Dandan; Ren, Beida; Liu, Shen; Xie, Xiaolong; Li, Chuanpeng; Song, Yuebo; Du, Yawei; Cao, Kegang; et al. (Frontiers in Pharmacology, 2021)
Background: Given the complexity of stroke treatment and the current widespread use of traditional Chinese medicine (TCM) in the absence of robust, large, long-term effectiveness and safety studies, and the lack of nationwide epidemiology and clinical characteristics of patients with stroke receiving TCM treatment, the acquisition of data from longitudinal cohorts is essential. We intend to generate the major clinical characteristics of patients with stroke who receive TCM treatment and to investigate the effectiveness and safety of TCM in the Chinese population. Methods: The China Stroke Registry for Patients with Traditional Chinese Medicine (CASES-TCM) study is a prospective, multicenter, observational disease registry aiming to register 20,000 hospitalized patients. Eligible adult patients with clearly diagnosed acute ischemic stroke or intracerebral hemorrhage within seven days of symptom onset will be consecutively registered from 126 participating sites across China. Baseline data will be recorded, and all patients will be regularly followed up at 3, 6, 12, and 24 months after stroke onset. Collected data will be entered into a web-based system with high-level data security. The primary outcomes include the distribution of scores on the modified Rankin Scale at the 3-month follow-up, and recurrent stroke events within the 12-month follow-up. Conclusion: To our knowledge, the CASES-TCM study is the first and largest nationwide registry to document comprehensive data on TCM treatment in patients with acute stroke. The findings of this study will be valuable to improve our knowledge about TCM treatment for patients with stroke and its subsequent outcomes in the actual clinical setting, consequently facilitating and standardizing the optimization of individualized interventions with TCM for stroke prevention and treatment in China. Study registration: This study was registered with Clinicaltrials.gov (URL: https://clinicaltrials.gov/, Unique identifier: NCT04921397).